Psychoanalytic Perspective on Coaching : Organization on a Couch - Barabasz, Adela (Coaching w ujęciu psychoanalitycznym, czyli lider na kozetce, 2010)
The paper will present the psychoanalytical basis for coaching, understood as the form of supporting advancement of managerial staff and also improvement of teams and the whole organization. Coaching is especially attractive in the context of the personality approach to organization and management, which is a subject of the author's interests and study. Considering organization through the personality prism in the psychoanalytic approach accentuates close connections between the problems of a leader with respect to coaching, and the difficulties experienced by the whole organization or team directed by the leader. Due to coaching sessions, one can understand how and in what way one person's dysfunctions generate dysfunctions in the scale of the whole organization.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 182-192
Keywords: coaching; psychoanalysis; management; development of an organisation